2001
DOI: 10.1590/s0037-86822001000100004
|View full text |Cite
|
Sign up to set email alerts
|

Retardo do crescimento em crianças com reação intradérmica positiva para leishmaniose: resultados preliminares

Abstract: Resumo O objetivo deste trabalho foi comparar a ingestão alimentar habitual e a freqüência de retardo do crescimento de crianças com reação intradérmica positiva para leishmaniose (Montenegro-positivas), com um grupo Montenegro-negativo. A ingestão alimentar habitual foi avaliada pelo recordatório de 24 horas e o retardo do crescimento definido segundo critérios da OMS. Crianças Montenegro-positivo (n = 9) e Montenegronegativo (n = 17) ingeriam, respectivamente, quantidades similares de energia (1456,8 ± 314,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…On the other hand, Viana et al [13] used both tests and did not observe any differences between the average age of positive and negative subjects. For studies which involved children only [32], [36], [44], [52], meta-analysis were not performed since the upper cut-off point was different between studies. In this case, no consistent patterns were identified in the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Viana et al [13] used both tests and did not observe any differences between the average age of positive and negative subjects. For studies which involved children only [32], [36], [44], [52], meta-analysis were not performed since the upper cut-off point was different between studies. In this case, no consistent patterns were identified in the results.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the potential role of malnutrition on the risk of infection by L. infantum we selected four papers reporting results of five studies which compared eutrophic children and those with some degree of malnutrition [32], [36], [48], [52]. Figure 4 shows that the presence of malnutrition (although non-significantly) decreased the likelihood of diagnosis of asymptomatic infection.…”
Section: Resultsmentioning
confidence: 99%
“…During the leishmaniasis infection, the impaired immune system of the host may cause an uncontrolled parasite replication that delays the healing of CL leading to a diffuse CL, ML or VL [6]. Even though it has been shown that leishmaniasis may occur in individuals in endemic areas independently of the nutritional status [7], studies with children have shown a link between poor Nutritional Status of Patients with Cutaneous Leishmaniasis from a Tropical Area of Bolivia, and Implications for Zinc Bioavailability 50 nutritional status, growth retardation and iron deficiency with CL [8,9]. Furthermore, malnourished children are at a greater risk for developing severe VL than well-nourished children [10].…”
Section: Introductionmentioning
confidence: 99%